2003
DOI: 10.1046/j.0024-4066.2002.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource polymorphism in a Patagonian fish Percichthys trucha (Percichthyidae): phenotypic evidence for interlake pattern variation

Abstract: Within‐species differentiation in phenotypic characters related to resource use (resource polymorphism) is frequently thought to result from divergent natural selection in a heterogeneous environment with ‘open niches’. In this study we found consistent resource‐based polymorphism within three different populations of Percichthys trucha , a lake‐dwelling fish native to the southern Andes. In each of three lakes we found two morphotypes that could be clearly distinguished by differences in gill raker length. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
58
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 48 publications
2
58
0
Order By: Relevance
“…Evolutionary biologists aim to understand the relative magnitudes of shared selective regimes, unique histories, and the interaction between these two evolutionary sources of diversification (e.g., Irschick et al 1997;Huey et al 2000;Matos et al 2002;Van Buskirk 2002;Ruzzante et al 2003;Blackledge and Gillespie 2004;Hendry et al 2006). Nonetheless, the explicit quantification and evaluation of the importance and nature of these mechanisms rarely has been attempted (Langerhans and DeWitt 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evolutionary biologists aim to understand the relative magnitudes of shared selective regimes, unique histories, and the interaction between these two evolutionary sources of diversification (e.g., Irschick et al 1997;Huey et al 2000;Matos et al 2002;Van Buskirk 2002;Ruzzante et al 2003;Blackledge and Gillespie 2004;Hendry et al 2006). Nonetheless, the explicit quantification and evaluation of the importance and nature of these mechanisms rarely has been attempted (Langerhans and DeWitt 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To advance our knowledge of replicated evolution among multiple groups of organisms, evolutionary biologists must move beyond simply examining the significance of shared responses to shared selective regimes. Understanding the factors that contribute to divergent evolution among species occupying shared selective regimes is essential if we are to fully appreciate the relative generality or peculiarity of evolutionary trends (e.g., Huey et al 2000;Gould 2002;Matos et al 2002;Van Buskirk 2002;Ruzzante et al 2003;Langerhans and DeWitt 2004;Hendry et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nominal species show a conspicuous morphological variation of the oropharyngeal apparatus-large and small mouths, and long and short gill rakes )-that are related to resource use (Logan 2000). The variation patterns are different in different lakes (Ruzzante et al 2003). Genetic studies have not yet found evidence of either specific differences or reproductive isolation between morphs , and some findings suggest that environmental cues plays a major role in determining oropharyngeal development.…”
Section: Influence Of Temporal Changes In Climate On Geological Scalesmentioning
confidence: 99%
“…Genetic studies have not yet found evidence of either specific differences or reproductive isolation between morphs , and some findings suggest that environmental cues plays a major role in determining oropharyngeal development. This variation can be identified during the juvenile period (Ruzzante et al 2003) and can also be observed among sibling larvae breeding in captivity, seemingly related with yolk amount (S. Crichigno, personal communication). Populations of 'perca' upstream and downstream of a hydroelectric dam can also show oropharyngeal differences, and these differences were identified within only a few years of the dam being built .…”
Section: Influence Of Temporal Changes In Climate On Geological Scalesmentioning
confidence: 99%